Acciones de control interno para mejorar la gestión institucional. caso: institución de microfinanzas "cendes" - Valderrama Araujo, Pedro Andrés (2016)
The purpose of this research is to investigate the actions of internal control to improve institutional management of the Microfinance Institution "CENDES". The problem was investigated How internal control actions will improve the institutional management of the Microfinance Institution "CENDES"? and the hypothesis is that the rules and actions of internal control of Microfinance Institution “CENDES” significantly improve the governance of the lender “CENDES”. The population or universe of study was the Institution Microfinance “CENDES” district of Santa and its sample was four managers and four credit analysts, and informants were two administrators, two industrial engineers are managers and two economists and two professional were credit analysts. The method used was descriptive, explanatory and analytical, and technical and instrument was the interview and the interview guide. The research design was a single box The results obtained was in the found situation in the area of internal control of the Institution entity Microfinance “CENDES” were important, as some errors and deficiencies in the credit area was found, improving its lending activities and that the institution microfinance study did not have an adequate system of internal control to ensure reliability in daily credit operations.